Facebook Support Groups for Pediatric Rare Diseases: Cross-Sectional Study to Investigate Opportunities, Limitations, and Privacy Concerns - Sarah Catrin Titgemeyer; Christian P Schaaf (JMIR Publications, 2022)
BackgroundBecause of the nature of rare diseases with affected individuals being widely geographically dispersed, finding an in-person/offline support group itself can be a challenge. Affected individuals therefore turn to social networking platforms such as Facebook for online support groups. ObjectiveWe aim to put into perspective the opportunities Facebook offers as a tool for pediatric rare disease support groups by investigating its use, advantages, and limitations including privacy concerns. We analyze group accessibility and usage, advantages specific to rare diseases, perceived privacy, and views on using Facebook for communication between health professionals and parents, pharmaceutical companies, and study recruitment. MethodsWe contacted 12 Facebook support groups for 12 respective rare diseases with pediatric onset and invited group members to participate in a cross-sectional online survey. ResultsOf 231 respondents, 87.0% (n=201) of respondents were female, 12.6% (n=29) were male, and 0.4% reported another sex (n=1). Respondents' mean age was 41.56 years (SD 9.375); 91.3% (n=211) of respondents were parents (183 mothers, 27 fathers, 1 other sex); 59.7% (n=138) reported a self-initiated search for the Facebook group, 24.2% (n=56) received recommendations from their health professionals, and 12.6% (n=29) recommendations from someone else affected by the disease. On average, support group members visited Facebook at least once a day, visited and passively participated (read/liked posts) several times a week, and participated actively (commented/posted) once a month. As much as 79.2% (183/231) agreed that they would like to have health professionals as members of the respective Facebook group. Group members expressed more concern about privacy issues on Facebook in general than in their respective Facebook support groups, with concerns mostly related to Facebook itself and nongroup members. ConclusionsOur study confirmed that Facebook enhances support group accessibility for parents of children with rare diseases. Group participants perceive a reduction and elimination of distance, a common challenge in rare disease, and Facebook support groups create an environment of perceived privacy. The group's privacy setting can be a critical factor for active support group participation. Sharing personal information and pictures on Facebook is very common among group participants, which shows the importance of discussing and protecting children's privacy rights in this context. Trial RegistrationGerman Clinical Trials Register DRKS00016067; https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00016067